2010
DOI: 10.1002/pds.1980
|View full text |Cite
|
Sign up to set email alerts
|

How are antibacterials used in nursing homes? Results from a point‐prevalence prescription study in 44 Norwegian nursing homes

Abstract: Antibiotics are often used in nursing homes, both as treatment and prophylaxis. The most common infections treated with antibiotics were UTIs, followed by RTIs. Choice of antibacterial, dosage and duration of treatment were in accordance with recommendations in guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 13 publications
3
25
1
5
Order By: Relevance
“…Although prescription of quinolone antibacterials was frequent (34.2%) in LTCFs, which can lead the increased presence of infections caused by Clostridium diffi cile and other antimicrobial resistant pathogens [22][23][24][25][26][27]. This result is similar to several overseas studies that quinolones are the most frequently prescribed antibacterials in LTCFs [20][21][22][23][24][25][26][27]. Among eligible residents receiving antibacterial agent for treatment of an infection, only 2.4% of prescriptions were based microbiologically results.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Although prescription of quinolone antibacterials was frequent (34.2%) in LTCFs, which can lead the increased presence of infections caused by Clostridium diffi cile and other antimicrobial resistant pathogens [22][23][24][25][26][27]. This result is similar to several overseas studies that quinolones are the most frequently prescribed antibacterials in LTCFs [20][21][22][23][24][25][26][27]. Among eligible residents receiving antibacterial agent for treatment of an infection, only 2.4% of prescriptions were based microbiologically results.…”
Section: Discussionsupporting
confidence: 75%
“…The prevalence of antimicrobial use among participating LTCFs was lower (1.3%) compared with results from other European surveys (2.4-15%) [3,11,[21][22][23]. National result showed that the prevalence of antimicrobial use was lower than the prevalence of infections, thus the overuse of antimicrobials is not common in participating LTCFs.…”
Section: Discussioncontrasting
confidence: 44%
“…Während in den aus skandinavischen Einrichtungen publizierten Prävalenzstudien zwar höhere Antibiotikaprävalenzen beschreiben werden, ist dort der Anteil an Chinolonen meist deutlich geringer. In der Regel werden dort Methenamine, Trimethoprim oder Nitrofurane zur Uroprophylaxe eingesetzt [17,19,20]. Ein ähnlich hoher Anteil an Fluorchinolonen (24 %) ist in 2010 aus der italienischen Prävalenzstudie im Rahmen von HALT in 92 Einrichtungen hervorgegangen [21].…”
Section: W U N D E N D E S O R I E N T I E R T H E I T E I N G E S C unclassified
“…Auch in anderen europäischen Län-dern ist die fortlaufende Dokumentation und Bewertung von HCAI in Altenpflegeheimen nicht etabliert, und es existieren nur einige wenige Prävalenzstudien zu HCAI in Altenpflegeheimen [11,12,13,14,15]. Zudem war es auch bisher nicht mög-lich, Aussagen über den Gebrauch von Antibiotika zu therapeutischen oder prophylaktischen Zwecken in Heimen zu machen.…”
Section: Originalien Und üBersichtenunclassified